2013
DOI: 10.1111/bcp.12127
|View full text |Cite
|
Sign up to set email alerts
|

E‐pharmacovigilance: development and implementation of a computable knowledge base to identify adverse drug reactions

Abstract: AIMSComputer-assisted signal generation is an important issue for the prevention of adverse drug reactions (ADRs). However, due to poor standardization of patients' medical data and a lack of computable medical drug knowledge the specificity of computerized decision support systems for early ADR detection is too low and thus those systems are not yet implemented in daily clinical practice. We report on a method to formalize knowledge about ADRs based on the Summary of Product Characteristics (SmPCs) and linkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
1
38
0
1
Order By: Relevance
“…E-pharmacovigilance (where a computer links a patient's medications with their laboratory results) can inform prescribers of potential ADRs in the setting of abnormal laboratory values [Neubert et al 2013]. This represents an important step towards a systematic drug safety process but requires clinician engagement, intensive resources and regular updates.…”
Section: Adr Prediction Toolsmentioning
confidence: 99%
“…E-pharmacovigilance (where a computer links a patient's medications with their laboratory results) can inform prescribers of potential ADRs in the setting of abnormal laboratory values [Neubert et al 2013]. This represents an important step towards a systematic drug safety process but requires clinician engagement, intensive resources and regular updates.…”
Section: Adr Prediction Toolsmentioning
confidence: 99%
“…This may include ongoing training and education at pre-service and in-service levels, involvement of Therapeutic Committees at facility and regional levels and introduction, for example, of innovative electronic reporting to improve efficiency and boost the response rate among healthcare workers. [19][20][21][22] In conclusion, the study revealed a high level of knowledge of pharmacovigilance and ADR reporting system among the healthcare workers, though this has informed neither their attitude nor their practice of ADR reporting as seen in their reported attitude and practice. In other to optimize the current system, there is a need for effective communications between TIPC and the healthcare workers; this may be in the form of feedback, continuing professional development (CPD) lectures, advocacy within the health sector and community engagement.…”
Section: Community Engagementmentioning
confidence: 71%
“…Depending on the setting, centralized, national reporting systems may not always be the solution to pharmacovigilance but if they are adopted—as is the case in Namibia—there is a need to continually support their function and improvement. This may include ongoing training and education at pre‐service and in‐service levels, involvement of Therapeutic Committees at facility and regional levels and introduction, for example, of innovative electronic reporting to improve efficiency and boost the response rate among healthcare workers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general standard and still the most commonly used method of ADR detection is mandatory spontaneous reporting (Neubert et al, 2013). In the USA, the primary source of such reports is the FDA Adverse Event Reporting System (FAERS) database (FDA, 2014) of the U.S. Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%